Watkins Family Christmas Photograph - Watkins, Howard::::::::: (1982)
Howard Watkins, Adam Watkins looking down at Robin, Christine Watkins holding Robin Watkins Adam's T-shirt: "ÄDAM Robin's Big Brother"